Lymphatic Metastasis and Sentinel Lymphonodectomy - Schlag, Peter M.; Veronesi, Umberto (Springer Berlin Heidelberg, 2000)
Metastases determine malignancy. The main attention so far has been focused upon organ metastases. The molecular mechanisms thereof, while far from being totally elucidated, are increasingly well understood. Modern diagnostic tools now enable detection and precise localization of small lesions. In contrast, our knowl edge and diagnostic capabilities regarding metastatic spread to the'lymphatic system are rather limited. However, there have re cently been a number of interesting advances. It is the aim of this volume to submit these developments to detailed analysis. The therapeutic relevance of enhanced sensitivity in detection of lymph node metastases has to be considered in the light of in creased morbidity versus eventual prognostic improvements by modification of therapy. An interesting concept which might im prove diagnostic accuracy while reducing operative morbidity is the "sentinel node" technique. Surgical standards are lacking, however, and many fundamental questions pertaining to precise lymphatic mapping remain unanswered. Whether the sentinel node concept is of general relevance or whether it is applicable in only a few organs remains to be determined. This book offers intensive discussion of the concept from methodological and tu mor biological viewpoints. World-renowned experts with long term involvement in related basic and clinical research provide the reader with a broad survey of actual knowledge together with a critical appraisal of recent and future developments. We sincerely hope this book succeeds in providing an outlook as a reference for all clinicians on future prospects and serving and researchers in this extremely important field
Keywords: Cancer Research; Oncology; General Surgery; Dermatology; Nuclear Medicine; Pathology; Oncology; Surgery; Nuclear medicine; Lymphknotenmetastase; Lymphknotenresektion; Aufsatzsammlung